Crystallization of micelles at chemically terminated interfaces - Hock, Rainer; et al. (Physical Review Letters, 2004)
In aqueous solutions and for high concentrations triblock copolymers are known to aggregate. As a critical volume fraction of micelles is reached they crystallize. We report on grazing incident small angle neutron scattering as an experimental tool to investigate the crystallization of spherical polymer micelles in the immediate vicinity of a flat solid interface. We find for an attractive surface potential a face centered close packed structure with a random orientation perpendicular to the normal of the interface. For a repulsive potential crystallization is suppressed.